Forecasting the Processes of Siltation of Flood Reservoirs - Yangiev, Аsror; Adjimuratov, Dilmurat; Panjiev, Sherzod (European Journal of Life Safety and Stability (2660-9630), 2022)
The article presents the results of field research conducted in Kasansay, Rezaksay and Jiydalisay flood reservoirs in Namangan region (Uzbekistan). The floods in the reservoirs are causing a lot of problems, and there are disturbances in the discharge and discharge facilities during the accidental floods. At the same time, a large amount of mud and sediments accumulated in the reservoirs. Clearing of flood reservoirs from mud and sediments will need to be considered on the basis of calculations. At present, it is necessary to determine the useful volume of flood reservoirs and consider the issue of targeted use of flood reservoirs in the future, given the loss of useful volume. The main purpose of the study is to forecast the amount of sludge in the flood reservoirs on the basis of natural observations and make recommendations for their removal. In the article, the results of the calculations using empirical formulas for predicting the amount of turbid sediments in Kasansay, Rezaksay and Jiydalisay flood reservoirs up to 2025-2030 years are also presented, and it is noted that at present their useless volumes are full of turbid sediments. Preliminary recommendations Ufor assessing the safety of flood reservoirs have been developed. It has been observed that the useless volumes of the above-mentioned flood reservoirs are now filled with mud and sediments and will increase in the future. Observations show that the particle size of sedimentary deposits is characterized by a decrease in the direction of the dam from the entrance to the floodplain. That is, in the upper storks, deposits consisting mainly of rock and sand particles collapse. In addition, the article provides information on initial recommendations for assessing the safety of flood reservoirs.